The crown of thorns of Notre-Dame de Paris, mythological representations of memory (diségno, 2021)
On April 15, 2019, the whole world found itself gathered, as happens few times and for long and interminable moments, around the images that transmitted from Paris: the cathedral of Notre-Dame de Paris, in its solid and immutable appearance, was wrapped inexorably from the fire that gradually caused the collapse of the iconic spire, roof, and limestone vaults (read more).